A Review of Fetal Scarless Healing. (17th May 2012) - Rolfe, K. J.; Grobbelaar, A. O.
Abstract : Wound healing is a complex process involving a number of processes. Fetal regeneration has been shown to have a number of differences compared to scar-forming healing. This review discusses the number of differences identified in fetal regeneration. Understanding these differences may result in new therapeutic targets which may reduce or even prevent scarring in adult healing.